Islamic Boarding School Education Leadership in Supporting Face to Face Learning During the Pandemic Period in Indonesia - Zulvia Trinova; Ade Iskandar; Irwan Fathurrochman; Antono Damayanto; Endang Fatmawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This study identified of school education leadership skills in supporting virtual learning approach during pandemic disruption. The author believes that online learning requires solid educational leadership, which can empower all potential and influence. Hence, learning objectives was affected by the Covid-19 pandemic run well. So, the researchers have visited several scientific publications on several application databases of educational leadership studies during the disruption of the pandemic several complications such as Eric Publications, Google book, Taylor and France, and many other publications actively discussing educational leadership issues during distance learning as a result of responding to the Covid-19 pandemic. While the review process involves several stages, first, giving coded the data, evaluated and looked for relevance, interpreted it in depth to conclude if the findings were relevant in answering valid questions. This study was entirely dependent on secondary data in the form of field details that have been published in various scientific publication journals, especially about educational leadership during pandemic disturbances. We found that there were a number of leadership educations was used to support virtual learning during pandemic as mention in finding section. Keywords: Virtual Learning, Learning Pandemic Time, Educational Leadership